2016
DOI: 10.1021/acsami.6b02963
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Functionalized Magnetic-Mesoporous Silica Nanoparticles for Drug/Gene Codelivery To Potentiate the Antitumor Efficacy

Abstract: An appropriate codelivery system for chemotherapeutic agents and nucleic acid drugs will provide a more efficacious approach for the treatment of cancer. Combining gene therapy with chemotherapeutics in a single delivery system is more effective than individual delivery systems carrying either gene or drug. In this work, we developed folate (FA) receptor targeted magnetic-mesoporous silica nanoparticles for the codelivery of VEGF shRNA and doxorubicin (DOX) (denoted as M-MSN(DOX)/PEI-FA/VEGF shRNA). Our data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…In addition, as a result of the slightly negative charge of MSNs-DOX@PDA-PEG, the overall clearance by the reticuloendothelial system (RES) such as liver was found to be reduced. 24,25 These data suggested that MSNs-DOX could be successfully synthesized and modied by introduction of PDA and PEG lms.…”
Section: Synthesis and Physicochemical Characterization Of Msns-dox@pmentioning
confidence: 92%
“…In addition, as a result of the slightly negative charge of MSNs-DOX@PDA-PEG, the overall clearance by the reticuloendothelial system (RES) such as liver was found to be reduced. 24,25 These data suggested that MSNs-DOX could be successfully synthesized and modied by introduction of PDA and PEG lms.…”
Section: Synthesis and Physicochemical Characterization Of Msns-dox@pmentioning
confidence: 92%
“…Silanol groups present on the surface of MSNs can be functionalized with various ligands, which could be one way of controlling nanoparticle (NP) biodistribution and the design of specific targeted delivery systems (Bouchoucha et al 2016;Li et al 2016). MSNs have been widely studied for their capability to load and release various drugs (Vallet-Reg ı, Balas, and Arcos 2007; Deodhar, Adams, and Trewyn 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Critical micellar concentration (CMC) of FPDP was determined using pyrene as the probe by uorescence spectroscopy (LS55, PerkinElmer). 20,[37][38][39] The particle size and zeta potential of FPDP, FPDP/DOX, FPDP/shBeclin1 and FPDP/DOX/shBeclin1 micelles were measured by dynamic light scattering (DLS) using Malvern Zetasizer NanoZS90 (Malvern instruments, UK). The morphology of micelles was observed by transmission electron microscopy (TEM, Tecnai G2 Spirit 120 kV).…”
Section: Preparation Of Micellesmentioning
confidence: 99%
“…In this contribution, a nanocarrier-based delivery system offers a platform for the co-delivery of siRNA (shRNA) and anticancer chemotherapeutics simultaneously to the same tumor cells. 16 In recent years, enormous efforts have been put into the development of novel siRNA (shRNA) and DOX co-delivery systems with enhanced bioavailability, low toxicity and prolonged circulation time, such as polymers, 11,17 liposomes, 18 dendrimers, 19 mesoporous silica nanoparticles 13,20,21 and quantum-dot (QD)-based nanoparticles. 22 Among those systems, the amphiphilic cationic copolymers are widely used due to their excellent biocompatibility, desirable biodegradability, and unique self-assembling property.…”
Section: Introductionmentioning
confidence: 99%